The Effect of Organizational Culture on Employee Loyalty - Yolanda Oktaviana Yusuf; Romat Saragih (Almana : Jurnal Manajemen dan Bisnis, 2020)
High employee loyalty is a big goal for each company because of the increasing competition between companies. To overcome the decline in employee loyalty and retain existing employees, the company must create a comfortable work environment. In addition to a comfortable environment, organizations must also build a strong organizational culture. This research was conducted to determine the effect of organizational culture on employee loyalty at PT. Tara Megah Muliatama or commonly known as Gemah Ripah Taxi. The purpose of this research is to know and analyze how the organizational culture in the company, how the loyalty of employees, especially drivers, and how much influence the organizational culture has on employee loyalty at PT. Tara Megah Muliatama. This study uses a quantitative method with a descriptive type of research - causality. The sample of this study was taken randomly as many as 78 respondents. The analysis technique used in this research is descriptive analysis and simple linear regression analysis. The data collection needed in this research is by distributing questionnaires to 78 drivers of Gemah Ripah Taxi. The regression test results show that organizational culture has a significant effect on employee loyalty. Meanwhile, the R square value on the coefficient of determination shows that organizational culture on employee loyalty is 16%, the remaining 84% is influenced by other factors that are not addressed in this study.